Phytochemical and pharmacological review of Erica Genus (L.) Ericaceae plants - Francis Adu-Amankwaah; Hleziphi V. Mpundu; Kudakwashe Nyambo; Paula Strauss; Kudzanai Ian Tapfuma; Ndivhuwo Tshililo; Motunrayo Victoria Badejo; Lawrence Mabasa; Vuyo Mavumengwana; Lucinda Baatjies (Phytomedicine Plus)
Background and Purpose: The Erica genus, part of the Ericaceae family, consists of diverse evergreen shrubs known for their vibrant floral displays and adaptation to nutrient-poor soils. Traditionally, these plants have been used for their pharmacological properties, including anti-inflammatory, antimicrobial and antioxidant effects. Despite their widespread ethnomedicinal use, a comprehensive review of the pharmacological potential of Erica species is still lacking. Study Design and Methods: This review presents an overview of the phytochemical, ethnomedicinal, pharmacological and toxicological properties of Erica species. A systematic literature search was conducted using online databases to identify primary studies on the Erica genus. Keywords such as “Erica,” “antioxidant,” “anti-inflammatory,” “toxicology,” “phytochemistry,” “anticancer,” “antidiabetic,” “antidiuretic,” “pharmacology,” “ethnomedicine” and “cytotoxicity” were employed. The search covered studies published from July 1980 to February 2023. All plant names were verified through ''The Plant List'' (http://www.theplantlist.org/) and PlantZAfrica (https://pza.sanbi.org/), while chemical structures were confirmed using ChemDraw Ultra and PubChem(https://pubchem.ncbi.nlm.nih.gov/). Over 60 bioactive compounds, including myricetin, rutin and luteolin, were identified, exhibiting anti-inflammatory, antioxidant, antimicrobial, antidiabetic and anticancer properties. Additionally, traditional uses of Erica plants by indigenous cultures in treating various ailments were documented, highlighting the importance of this genus in ethnomedicine. Conclusion: This review provides a comprehensive reference for researchers, offering insights into the therapeutic potential of Erica species and guiding future investigations into their pharmacological benefits.